2017
DOI: 10.11591/ijece.v7i2.pp912-918
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trend in Electromagnetic Radiation and Compliance Assessments for 5G Communication

Abstract: The deployment of the 5G networks will feature high proliferation of radio base station (RBS) in order to meet the increasing demand for bandwidth and also to provide wider coverage that will support more mobile users and the internet-of-things (IoT). The radio frequency (RF) waves from the large-scale deployment of the RBS and mobile devices will raise concerns on the level of electromagnetic (EM) radiation exposure to the public. Hence, in this paper, we provide an overview of the exposure limits, discuss so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The progress in wireless technologies has made human exposure to electromagnetic fields (EMFs) increasingly complex, so, monitoring EMF exposure levels and characterizing them are indispensable for risk communications of human exposure to EMFs [33], [34]. Various studies showed that respondents had experienced significant and negative effects of radio frequency radiation (RFR) on their mental health, indicating a critical and urgent need to educate the public on the subject [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…The progress in wireless technologies has made human exposure to electromagnetic fields (EMFs) increasingly complex, so, monitoring EMF exposure levels and characterizing them are indispensable for risk communications of human exposure to EMFs [33], [34]. Various studies showed that respondents had experienced significant and negative effects of radio frequency radiation (RFR) on their mental health, indicating a critical and urgent need to educate the public on the subject [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure limit for power density for ICNIRP for frequency above 10 GHz is 10 W/m2, 50 W/m2 for public and occupational values, respectively. The power density of the FCC for frequency above 6 GHz is 10 W/m2 for public value [12].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in fifth-generation (5G) networks, the current major concern is the green communications without making a tradeoff with other performance metrics like spectrum efficiency (SE) and latency [5][6][7][8][9][10][11][12][13][14]. Millimeter wave (mm-wave) solution is adopted in concentrated-coverage base stations (BSs) for loading the massive backhaul traffic [15][16][17][18][19]. Nonetheless, it is a significant contribution to realize such traffic load in a low energy consumption way [20].…”
Section: Introductionmentioning
confidence: 99%